Analisis Komunikasi Organisasi di Pusat Informasi Haji Kantor Wilayah Kementerian Agama Provinsi Sumatera Selatan - Syahir Badrudin; Muslimin Muslimin; Herry Okta Pratama (Program Studi Komunikasi dan Penyiaran Islam UIN Raden Fatah Palembang, 2017)
Analysis of Organizational Communication at the Haj Information Center Regional Office of the Ministry of Religious Affairs of South Sumatra Province. Looking at the above context then the question arises, how the organization communication in the Haj Information Center Regional Office of the Ministry of Religious South Sumatra Province ?. On the basis of problems that have been formulated it can be determined that the purpose of research is to know and get a picture of organizational communication in the Haj Information Center Regional Office of the Ministry of Religious Affairs of South Sumatra Province. Researchers see the existence of clear communication includes processes, messages, networks and interdependent circumstances. This research is categorized in qualitative descriptive research. Descriptive means simply describing the situation and events. Qualitative communication research is usually not intended to provide explanations, control the symptoms of communication, put forward a picture or understanding of how and why a symptom or reality of communication occurs. From the results of research that has been done, found the data that the Organization's communication at the Haj Information Center Office of the Ministry of Religious Affairs runs well. This can be seen from the translation process, message, network, and state of interdependence.